PDGFR-modulated miR-23b cluster and miR-125a-5p suppress lung tumorigenesis by targeting multiple components of KRAS and NF-kB pathways. Issue 1 (December 2017) - Naidu, Srivatsava; Shi, Lei; Magee, Peter; Middleton, Justin; Laganá, Alessandro; Sahoo, Sudhakar; Leong, Hui; Galvin, Melanie; Frese, Kristopher; Dive, Caroline; Guzzardo, Vincenza; Fassan, Matteo; et al.
Abstract In NSCLC alterations in PDGF receptors are markers of worst prognosis and efficient targeting of these receptors is yet to be achieved. In this study, we explored PDGFR-regulated microRNAs demonstrating that miR-23b cluster and miR-125a-5p are downregulated by increased expression of PDGFR-α or PDGFR-β in NSCLC cells. Mechanistically, the expression of these microRNAs is positively regulated by p53 and negatively modulated by NF-kB p65. Forced expression of miR-23b cluster or miR-125a-5p enhanced drug sensitivity and suppressed invasiveness of NSCLC cells by silencing several genes involved in oncogenic KRAS and NF-kB pathways, including SOS1, GRB2, IQGAP1, RALA, RAF-1, IKKβ, AKT2, ERK2 and KRAS itself. Of note, an inverse correlation between miR-23b cluster, miR-125a-5p and respective target genes was also foundin vivo in a large dataset of lung adenocarcinoma samples. Furthermore, in vivo delivery of miR-23b cluster or miR-125a-5p significantly repressed tumour growth in a highly aggressive NSCLC circulating tumour cell (CTC) patient derived explant (CDX) mouse model. In conclusion, our finding sheds light on the PDGFR signaling and endorses the possibility to employ miR-23b cluster and miR-125a-5p as therapeutic tools to silence simultaneously a range of redundant pathways and main effectors of tumorigenesis in NSCLC.